Performance of WCN diffusion barrier for Cu multilevel interconnects - Lee, Seung Yeon; Ju, Byeong-Kwon; Kim, Yong Tae (IOP PUBLISHING LTD, 2018)
The electrical and thermal properties of a WCN diffusion barrier have been studied for Cu multilevel interconnects. The WCN has been prepared using an atomic layer deposition system with WF6-CH4-NH3-H-2 gases and has a very low resistivity of 100 mu Omega cm and 96.9% step coverage on the high-aspect-ratio vias. The thermally stable WCN maintains an amorphous state at 800 degrees C and Cu/WCN contact resistance remains within a 10% deviation from the initial value after 700 degrees C. The mean time to failure suggests that the Cu/WCN interconnects have a longer lifetime than Cu/TaN and Cu/WN interconnects because WCN prevents Cu migration owing to the stress evolution from tensile to compressive. (C) 2018 The Japan Society of Applied Physics.
Keywords: ATOMIC LAYER DEPOSITION; THROUGH-SILICON; PULSE PLASMA; THIN-FILMS; ELECTROMIGRATION; TSV; TAN; RELIABILITY; DEPENDENCE; STRESS